Prognosis of Biliary Atresia Associated With Cytomegalovirus: A Meta-Analysis - Yilin Zhao (Frontiers in Pediatrics, 2021)
Objective: The etiology of biliary atresia is unclear, but viral infection has been implicated. The aim of the current meta-analysis was to investigate relationships between cytomegalovirus (CMV) and the prognosis of biliary atresia.Methods: PubMed, Embase, the Cochrane Library, the China National Knowledge Infrastructure database, and Wanfang Data electronic databases were searched for eligible studies. Each relevant text was thoroughly reviewed and examined, including related papers in their reference lists.Results: A total of nine studies including 784 patients were included in the analysis. Biliary atresia patients with CMV exhibited significantly lower jaundice clearance (odds ratio: 0.46, p < 0.0001; I2 = 15%, p = 0.31). There were no significant differences in the rates of cholangitis or native liver survival. CMV-pp65-positive biliary atresia patients had a significantly lower rate of jaundice clearance (odds ratio: 5.87, p = 0.003; I2 = 0%, p = 0.71) and a significantly higher rate of cholangitis (odds ratio: 0.21, p = 0.01; I2 = 0%, p = 0.43) than CMV antibody-positive biliary atresia patients.Conclusion: Biliary atresia patients who were also infected with CMV had a poorer prognosis, particularly with respect to jaundice clearance. CMV status may influence the prognosis of biliary atresia. Clinicians should be able to routinely identify the subset of biliary atresia patients who are also CMV-positive, in order to improve native liver survival.